Seal san Aetóip : Sa Tóir ar Áirc an Chonartha. - Reidy, Frank (Cló lar-Chonnacht, 2013)
In this book Frank Reidy follows the journey of the Ark from Jerusalem to Ethiopia. He goes through the history and the folklore surrounding the Ark in legend.